2000
DOI: 10.1055/s-0042-1748126
|View full text |Cite
|
Sign up to set email alerts
|

Musical Backgrounds, Listening Habits, and Aesthetic Enjoyment of Adult Cochlear Implant Recipients

Abstract: This paper describes the listening habits and musical enjoyment of postlingually deafened adults who use cochlear implants. Sixty-five implant recipients (35 females, 30 males) participated in a survey containing questions about musical background, prior involvement in music, and audiologic success with the implant in various listening circumstances. Responses were correlated with measures of cognition and speech recognition. Sixty-seven implant recipients completed daily diaries (7 consecutive days) in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(59 citation statements)
references
References 15 publications
2
53
2
2
Order By: Relevance
“…These technological and physiological constraints limit how music is transmitted by the implant and, consequently, limits music enjoyment for cochlear implant users. Studies have assessed adult cochlear implant user’s listening habits and music enjoyment through questionnaires ( Gfeller et al, 2000 ; Looi and She, 2010 ). They found that many were dissatisfied and spent less time listening to music post-implantation.…”
Section: Introductionmentioning
confidence: 99%
“…These technological and physiological constraints limit how music is transmitted by the implant and, consequently, limits music enjoyment for cochlear implant users. Studies have assessed adult cochlear implant user’s listening habits and music enjoyment through questionnaires ( Gfeller et al, 2000 ; Looi and She, 2010 ). They found that many were dissatisfied and spent less time listening to music post-implantation.…”
Section: Introductionmentioning
confidence: 99%
“…These perceptual challenges largely stem from technological and anatomical limitations with CIs, including reduced frequency resolution due to broad bandpass filtering, a limited CI frequency input range, and imprecise electrical stimulation of the auditory nerve ( Limb & Roy, 2014 ). These factors may contribute to the decreased music enjoyment that many CI users experience, especially for individuals who used to enjoy music with normal acoustic hearing ( Gfeller et al, 2000 ; Migirov et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Music provides emotional stability and enhances life satisfaction in humans, and CI users consider it to be the second most important acoustic stimulus after speech [ 7 , 8 ]. Music has a wider dynamic range and frequency spectrum than speech [ 7 , 9 ], and the signal processing mechanisms of a CI can lead CI users to experience difficulty in enjoying the wide acoustic spectrum of music [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Music has a wider dynamic range and frequency spectrum than speech [ 7 , 9 ], and the signal processing mechanisms of a CI can lead CI users to experience difficulty in enjoying the wide acoustic spectrum of music [ 10 ]. Previous studies have shown that after CI surgery, many recipients avoid listening to music due to a decrease in their music appreciation compared with the satisfaction experienced before hearing loss [ 8 ].…”
Section: Introductionmentioning
confidence: 99%